An anti-glare film, photovoltaic module

CN122901983APending Publication Date: 2026-10-13JA SOLAR NEW ENERGY YANGZHOU CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610781949.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-02
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种防眩光膜、光伏组件,以解决光伏组件的眩光造成光污染、光能浪费、防眩光可靠性差的技术问题之一

Benefits of technology

[0015]本发明示例性实施例中提供的一个或多个技术方案中,至少可实现如下有益效果之一。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122901983A_ABST
    Figure CN122901983A_ABST
Patent Text Reader

Abstract

The application provides an anti-dazzle film and a photovoltaic module, and relates to the technical field of photovoltaics, and aims to solve one of the technical problems of the anti-dazzle film, i.e., the glare of the photovoltaic module causes light pollution, light energy waste, and poor reliability of the anti-dazzle film. The anti-dazzle film comprises a functional layer, and the functional layer comprises at least three anti-dazzle layers stacked together; the refractive index of each anti-dazzle layer is gradually decreased in sequence along the direction away from the incident light. The anti-dazzle film can reduce glare, has high reliability, and has high light energy utilization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photovoltaic technology, and in particular to an anti-glare film and a photovoltaic module. Background Technology

[0002] As a key component of solar photovoltaic power generation systems, photovoltaic modules are prone to glare in practical use due to the cover glass. Glare not only causes light pollution to the surrounding environment, interfering with people's normal lives and work, but also reduces the power generation efficiency of photovoltaic glass modules.

[0003] The statements in this section are merely background information related to the present invention and do not necessarily constitute prior art. Summary of the Invention

[0004] The purpose of this invention is to provide an anti-glare film and a photovoltaic module to solve one of the technical problems of light pollution, light energy waste, and poor reliability of anti-glare in photovoltaic modules.

[0005] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides an anti-glare film comprising a functional layer, wherein the functional layer comprises at least three anti-glare layers stacked together, and the refractive index of each anti-glare layer decreases sequentially along a direction away from the incident light.

[0006] According to at least one embodiment of the present invention, the difference in refractive index between two adjacent anti-glare layers ranges from 0.02 to 0.04.

[0007] According to at least one embodiment of the present invention, the number of anti-glare layers is three, and along the direction away from the incident light, the three anti-glare layers are respectively a first layer, a second layer, and a third layer; The refractive index of the first layer ranges from 1.47 to 1.49; the refractive index of the second layer ranges from 1.44 to 1.46; and the refractive index of the third layer ranges from 1.40 to 1.43.

[0008] According to at least one embodiment of the present invention, the total thickness of the functional layer ranges from 6 μm to 10 μm; and / or, The thickness of each anti-glare layer ranges from 2μm to 4μm.

[0009] According to at least one embodiment of the present invention, the anti-glare layer is formed by curing a composition, and the composition comprises, by weight, 49 to 66 parts of resin matrix, 9 to 24 parts of nanoparticles, 13 to 19 parts of diluent, 3 to 5 parts of photoinitiator and 5 to 8 parts of solvent.

[0010] According to at least one embodiment of the present invention, the resin matrix is ​​one or a combination of two of acrylic resin and silicone-modified acrylic resin in any proportion; and / or, The nanoparticles are barium titanate particles with a particle size of 50 nm to 100 nm; and / or, The diluent is one or a combination of two of trimethylolpropane triacrylate and ethoxylated trimethylolpropane triacrylate in any proportion; and / or, The photoinitiator is one or a combination of two of photoinitiator 1173 and photoinitiator 184 in any proportion; and / or, The solvent is a mixture of ethyl acetate and propylene glycol methyl ether acetate.

[0011] According to at least one embodiment of the present invention, in the composition of the first layer, the resin matrix is ​​an organosilicon-modified acrylic resin, the resin matrix is ​​49 parts to 56 parts, the nanoparticles are 19 parts to 24 parts, the diluent is 13 parts to 19 parts, the photoinitiator is 3 parts to 5 parts, and the solvent is 5 parts to 8 parts; and / or, In the composition of the second layer, the resin matrix is ​​a silicone-modified acrylic resin and an acrylic resin, the resin matrix is ​​56 to 61 parts, the nanoparticles are 13 to 18 parts, the diluent is 13 to 19 parts, the photoinitiator is 3 to 5 parts, and the solvent is 5 to 8 parts; and / or, In the composition of the third layer, the resin matrix is ​​silicone-modified acrylic resin and acrylic resin, the resin matrix is ​​58 to 66 parts, the nanoparticles are 9 to 15 parts, the diluent is 13 to 19 parts, the photoinitiator is 3 to 5 parts, and the solvent is 5 to 8 parts.

[0012] According to at least one embodiment of the present invention, the anti-glare film further includes: A release layer, wherein the release layer is disposed on the incident light side of the functional layer; A weather-resistant layer is disposed between the release layer and the functional layer; An adhesive layer is disposed on the side of the functional layer opposite to the release layer; A protective layer is disposed on the side of the adhesive layer opposite to the functional layer.

[0013] According to at least one embodiment of the present invention, the thickness of the release layer ranges from 26 μm to 78 μm; and / or, The thickness of the weather-resistant layer ranges from 25 μm to 45 μm; and / or, The thickness of the adhesive layer ranges from 18 μm to 28 μm; and / or, The thickness of the protective layer ranges from 25 μm to 75 μm; and / or, The release layer is composed of a PET film and a fluorinated release agent coating; and / or, The weather-resistant layer is made of polyester, acrylic, or epoxy-modified resin; and / or, The adhesive layer is prepared by adding nano-montmorillonite to a polyurethane-acrylate copolymer emulsion as the base material; and / or, The protective layer is made of polyethylene.

[0014] In a second aspect, the present invention provides a photovoltaic module, including a cover glass and an anti-glare film disposed on the incident light side of the cover glass, wherein the anti-glare film is the anti-glare film described in the first aspect.

[0015] In one or more technical solutions provided in the exemplary embodiments of the present invention, at least one of the following beneficial effects can be achieved.

[0016] The anti-glare film provided in the exemplary embodiment of the present invention exhibits a continuous gradient decrease in refractive index among its anti-glare layers along a direction away from the incident light, i.e., from the upper surface to the lower surface of the functional layer. This means that the refractive index difference between adjacent anti-glare layers is equal, thereby eliminating or minimizing abrupt changes in refractive index at the interface. Specifically, when light passes through the interfaces of each layer, the intensity and phase of the reflected light are highly consistent. These reflected lights undergo destructive interference, thereby minimizing the total reflectivity. In other words, while achieving optimal light transmittance, it also provides excellent anti-glare performance.

[0017] Furthermore, the anti-glare film of the exemplary embodiment of the present invention can be formed into a film with a release layer, and then the anti-glare film can be attached to photovoltaic modules or other glass requiring anti-glare by heat transfer printing. This type of anti-glare film is not only suitable for flat photovoltaic glass, but can also be applied to curved photovoltaic modules, expanding the application scenarios. At the same time, the anti-glare film can be adapted to the segmented heat lamination process in the photovoltaic module production process, without the need for secondary processing, which simplifies the production process compared to conventional glare films or coatings. Attached Figure Description

[0018] The accompanying drawings illustrate exemplary embodiments of the invention and, together with the description thereof, serve to explain the principles of the invention. These drawings are included to provide a further understanding of the invention and are incorporated in and constitute a part of this specification.

[0019] Figure 1 This is a schematic diagram of the structure of an anti-glare film according to an embodiment of the present invention. Detailed Implementation

[0020] In related technologies, surface microstructure etching is usually used to solve the glare problem of the cover glass of photovoltaic modules. However, this process is complex, costly and difficult to ensure consistency in large-scale production. Coating is used in some cases, but the coating has poor durability, which leads to a gradual weakening of the anti-glare effect.

[0021] To address the aforementioned issues, the anti-glare film provided by the exemplary embodiment of the present invention can be made into a film and precisely laminated onto the surface of photovoltaic glass through a thermal transfer process, which has the advantages of simple process, low cost and stable anti-glare performance.

[0022] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments.

[0023] An exemplary embodiment of the present invention provides an anti-glare film comprising a functional layer, the functional layer comprising at least three anti-glare layers stacked together, wherein the refractive index of each anti-glare layer decreases sequentially along a direction away from the incident light.

[0024] When anti-glare film is used for anti-glare treatment on the cover glass surface of photovoltaic modules, it must not only have a certain glare suppression rate but also excellent light transmittance to ensure that the photovoltaic modules maximize light capture efficiency while suppressing glare.

[0025] In practical applications, the functional layer consists of three or more anti-glare layers stacked together, for example, three, four, five, six, or more anti-glare layers. Along the direction away from the incident light, i.e., from the top surface to the bottom surface of the functional layer, the refractive index of each anti-glare layer decreases continuously in a gradient. This means the refractive index difference between adjacent anti-glare layers is equal, thus eliminating or minimizing abrupt changes in refractive index at the interface. Specifically, when light passes through the interfaces of each layer, the intensity and phase of the reflected light are highly consistent. These reflected lights undergo destructive interference, thereby minimizing the total reflectivity, resulting in excellent anti-glare performance while maintaining optimal light transmittance. If the refractive index difference between adjacent anti-glare layers is unequal, the intensity and phase of the reflected light at each interface no longer match, the destructive interference effect is destroyed, the total reflectivity increases significantly, and the anti-glare effect weakens.

[0026] For example, the difference in refractive index between two adjacent anti-glare layers ranges from 0.02 to 0.04, such as 0.02, 0.022, 0.024, 0.026, 0.028, 0.03, 0.032, 0.034, 0.036, 0.038, 0.04, or any two of the above values. This functional layer achieves step-like scattering of light through continuous variation in refractive index, which can reduce the problem of concentrated reflected light in traditional single-refractive-index layers.

[0027] For example, the total thickness of the functional layer ranges from 6μm to 10μm, such as 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, or any two of the above values. When the total thickness of the functional layer is too thin (less than 6μm), a sufficient refractive index gradient depth cannot be formed, and the anti-glare effect is poor; while when the total thickness of the functional layer is too thick (greater than 10μm), the anti-glare effect tends to be stable, but the light transmittance will decrease sharply.

[0028] For example, the thickness of each anti-glare layer ranges from 2μm to 4μm, such as 2μm, 2.2μm, 2.4μm, 2.6μm, 2.8μm, 3μm, 3.2μm, 3.4μm, 3.6μm, 3.8μm, 4μm or any two of the above values.

[0029] It should be noted that the thickness of each anti-glare layer can be the same or different.

[0030] The following description uses a functional layer consisting of three anti-glare layers as an example. Along the direction away from the incident light, the three anti-glare layers are the first layer, the second layer, and the third layer.

[0031] For example, the refractive index of the first layer ranges from 1.47 to 1.49, and can be, for example, 1.47, 1.472, 1.474, 1.476, 1.478, 1.48, 1.482, 1.484, 1.486, 1.488, 1.49, or within any two of the above values.

[0032] The refractive index of the second layer ranges from 1.44 to 1.46, for example, it can be 1.44, 1.442, 1.444, 1.446, 1.448, 1.45, 1.452, 1.454, 1.456, 1.458, 1.46 or any two of the above values.

[0033] The refractive index of the third layer ranges from 1.40 to 1.43, for example, it can be 1.40, 1.402, 1.404, 1.406, 1.408, 1.41, 1.412, 1.414, 1.416, 1.418, 1.42, 1.422, 1.424, 1.426, 1.428, 1.43, or any two of the above values.

[0034] In some embodiments, the anti-glare layer is formed by curing a composition comprising a resin matrix, nanoparticles, a diluent, a photoinitiator, and a solvent. The composition may be formed into a coating liquid and applied onto a release layer in a coating form and cured into a film.

[0035] The resin matrix is ​​one or a combination of two of acrylic resin and silicone-modified acrylic resin in any proportion; the nanoparticles are barium titanate nanoparticles; this composite system of resin matrix and barium titanate nanoparticles exhibits excellent UV aging resistance. The amount of barium titanate nanoparticles added can adjust the refractive index of the formed film. For example, the particle size of the barium titanate nanoparticles is 50 nm to 100 nm, and the refractive index is 2.39 to 2.41.

[0036] Unless otherwise specified, the solid content of acrylic resin or silicone-modified acrylic resin is 60%.

[0037] The diluent is one or a combination of two of trimethylolpropane triacrylate (TMPTA) and ethoxylated trimethylolpropane triacrylate (EO-MPTA) in any proportion; as a crosslinking monomer, the diluent can improve the curing rate and crosslinking density of the coating liquid, while adjusting the viscosity of the coating liquid and maintaining the smoothness of the coating.

[0038] The photoinitiator is one or a combination of two of photoinitiators 1173 and 184 in any proportion; the photoinitiator can rapidly decompose under UV irradiation to generate free radicals, which initiate the polymerization reaction of the resin matrix and the reactive diluent.

[0039] The solvent is a mixture of ethyl acetate and propylene glycol methyl ether acetate, exemplarily in a mass ratio of 3:1. This solvent effectively dissolves the components and has a moderate evaporation rate, preventing defects such as pinholes and craters from occurring during the coating process.

[0040] It should be noted that, unless otherwise specified, all components of the above composition are commercially available products.

[0041] In some embodiments, the composition forming the anti-glare layer, by weight, includes the following components and their contents: The resin matrix is ​​49 to 66 parts, for example, it can be 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts or within any two of the above values; The nanoparticles are in the range of 9 to 24 parts, for example, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 parts or within any two of the above values. The diluent is 13 to 19 parts, for example, 13, 14, 15, 16, 17, 18, or 19 parts, or within any two of the above values; The photoinitiator is 3 to 5 parts, for example, it can be 3 parts, 4 parts, 5 parts or within any two of the above values; The solvent is 5 to 8 parts, for example, 5, 6, 7, or 8 parts, or within any two of the above values.

[0042] Specifically, the components and their amounts in the composition forming the first layer are as follows: The resin matrix consists of 49wt%–56wt% organosilicon-modified acrylic resin (containing high-refractive-index siloxane segments in its molecular structure); 19wt%–24wt% barium titanate nanoparticles; 13wt%–19wt% diluent; 3wt%–5wt% photoinitiator; and 5wt%–8wt% solvent, which is a mixture of ethyl acetate and propylene glycol methyl ether acetate (mass ratio 3:1).

[0043] The components and their amounts in the composition that forms the second layer: The resin matrix consists of 56wt%–61wt% silicone-modified acrylic resin and ordinary acrylic resin (mass ratio 7:3); 13wt%–18wt% barium titanate nanoparticles; 13wt%–19wt% diluent; 3wt%–5wt% photoinitiator; and 5wt%–8wt% solvent, which is a mixture of ethyl acetate and propylene glycol methyl ether acetate (mass ratio 3:1).

[0044] The components and their amounts in the composition that forms the third layer: The resin matrix consists of 58wt%–66wt% silicone-modified acrylic resin and ordinary acrylic resin (mass ratio 3.5:6.5); 9wt%–15wt% barium titanate nanoparticles; 13wt%–19wt% diluent; 3wt%–5wt% photoinitiator; and 5wt%–8wt% solvent, which is a mixture of ethyl acetate and propylene glycol methyl ether acetate (mass ratio 3:1).

[0045] As can be seen from the component contents of the compositions forming the first to third layers, the composite system formed by the resin matrix and nanoparticles can adjust the refractive index of the cured film. Specifically, the higher the content of the silicone-modified acrylic resin, the higher the refractive index; similarly, the higher the content of the nanoparticles, the higher the refractive index. To reduce the refractive index from 1.48 in the first layer to 1.42 in the third layer, the refractive index of the resin matrix is ​​lowered by increasing its content and the proportion of ordinary acrylic resin within it. Furthermore, increasing the proportion of barium titanate nanoparticles further reduces the refractive index of the composition, thus forming an anti-glare layer with a progressively decreasing refractive index.

[0046] It is understandable that if the content of each component in the first to third layers is within the corresponding range, the film layer will have the corresponding refractive index after coating and curing.

[0047] Figure 1 This is a schematic diagram of the structure of an anti-glare film according to an embodiment of the present invention. Figure 1 As shown, the anti-glare film of an exemplary embodiment of the present invention further includes: a release layer disposed on the incident light side of the functional layer; a weather-resistant layer disposed between the release layer and the functional layer; an adhesive layer disposed on the side of the functional layer opposite to the release layer; and a protective layer disposed on the side of the adhesive layer opposite to the functional layer.

[0048] The surface of the anti-glare film on the side where the incident light is incident is the top surface, and the surface on the side away from the incident light is the bottom surface. From the top surface to the bottom surface, a release layer, a weather-resistant layer, a functional layer, an adhesive layer, and a protective layer are stacked in sequence.

[0049] For example, the thickness of the release layer ranges from 26μm to 78μm, such as 26μm, 31μm, 36μm, 41μm, 46μm, 51μm, 56μm, 61μm, 66μm, 71μm, 76μm or any two of the above values.

[0050] The thickness of the weather-resistant layer ranges from 25μm to 45μm, for example, it can be 25μm, 30μm, 35μm, 40μm, 45μm or any two of the above values.

[0051] The thickness of the adhesive layer ranges from 18μm to 28μm, for example, it can be 18μm, 20μm, 22μm, 24μm, 26μm or 28μm or within any two of the above values.

[0052] The thickness of the protective layer ranges from 25μm to 75μm, for example, it can be 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm or any two of the above values.

[0053] In some embodiments, the release layer is composed of a PET film and a fluorinated release agent coating.

[0054] Specifically, the release layer is composed of a biaxially oriented PET film and a fluorinated release agent coating. The PET film thickness ranges from 25μm to 75μm, and the fluorinated release agent coating thickness ranges from 1μm to 3μm, with a width ranging from 1100mm to 1600mm. This release layer combines the supporting function of the PET base layer with the release function, eliminating the need for a separate release layer structure in traditional applications. Controllable peel force is achieved through the molecular design of the fluorinated release agent, allowing for smooth and residue-free removal after heat transfer.

[0055] Fluorinated release agents can be acrylate fluororesins containing perfluoroalkyl ether segments, such as Daikin Industries' OPTOOL DSX series.

[0056] In some embodiments, the weather-resistant layer is made of polyester, acrylic, or epoxy-modified resin.

[0057] Specifically, the weather-resistant layer is formed by coating a PET release film with thermosetting weather-resistant resins, such as polyester, acrylic, and epoxy-modified resins. After curing, it has good light transmittance and puncture resistance, protecting the inner anti-glare layer from damage.

[0058] In some embodiments, the adhesive layer is prepared by adding nano-montmorillonite to a polyurethane-acrylate copolymer emulsion as a base material.

[0059] Specifically, the adhesive layer uses polyurethane-acrylate copolymer emulsion as the base material and adds 1% to 3% by mass of nano-montmorillonite as a reinforcing phase. This adhesive layer has an elongation of 200% to 300% and exhibits thixotropic flowability during thermal transfer (thermal lamination of photovoltaic modules). It can fill the micro-unevenness on the surface of the cover glass and buffer the stress caused by temperature changes, thus solving the problem of traditional adhesive layers easily lifting due to thermal expansion and contraction.

[0060] In some implementations, the protective layer is made of polyethylene.

[0061] In some embodiments, the anti-glare film of the exemplary embodiments of the present invention can be formed into a film with a release layer, and then the anti-glare film can be attached to photovoltaic modules or other glass requiring anti-glare by thermal transfer. This type of anti-glare film is not only suitable for flat photovoltaic glass, but also for curved photovoltaic glass, expanding its application scenarios. At the same time, the anti-glare film can be adapted to the segmented thermal lamination process in the photovoltaic module production process, eliminating the need for secondary processing and simplifying the production process compared to conventional glare films or coatings.

[0062] The following describes the preparation method of the anti-glare film, including the following steps: Step S1: Preparation of the release layer.

[0063] The PET substrate is subjected to corona treatment; the fluorinated release agent is evenly coated onto the PET substrate using an anilox roller coating method; and the release layer is obtained by drying and curing.

[0064] Step S2: Preparation of the weather-resistant layer.

[0065] Thermosetting resin is evenly coated onto the surface of the release layer, and then dried and cured to obtain a weather-resistant layer.

[0066] Step S3: Preparation of functional layers.

[0067] Step S31: Using a multi-channel doctor blade coater, place three coating liquids (compositions) with different refractive indices (first layer to third layer) into the coater; Step S32: Pass the release layer with weather-resistant layer obtained in step S2 through the coating machine at a uniform speed. Each channel of the coating machine is equipped with a thermosetting channel. The speed of the coating machine is 5m / min to 10m / min. Step S33: The first coating unit applies the first layer of coating liquid to the weather-resistant layer; the second coating unit applies the second layer of coating liquid to the surface of the first layer that has not fully cured; and finally, the third coating unit applies the third layer of coating liquid. Step S34: After coating, the composite structure enters the UV curing tunnel and cures for 3 to 5 minutes to obtain a release layer with functional layers.

[0068] Step S4: Preparation of the adhesive layer and protective layer.

[0069] The components of the adhesive layer are evenly coated onto the functional layer obtained in step S3, and dried at 60℃~70℃ for 1min~2min until the surface is no longer sticky. Then, a protective layer (PE film) is applied, and finally, the film is rolled up to obtain a complete anti-glare film.

[0070] The present invention also provides a photovoltaic module, including a cover glass and an anti-glare film disposed on the incident light side of the cover glass, wherein the anti-glare film is the anti-glare film in any of the above embodiments (excluding the release layer and the protective layer).

[0071] For example, the practical applications of anti-glare film in photovoltaic modules are as follows: Photovoltaic modules are typically made by stacking cover glass, encapsulant film, photovoltaic cells, another encapsulant film, and backsheet in sequence, and then laminating them in a laminator to form a laminate.

[0072] When applying anti-glare film, the film is cut to the same size as the cover glass. The protective layer is peeled off, and the film is adhered to the edge of the cover glass. Then, the cover glass with the anti-glare film, the adhesive film, the photovoltaic cells, another adhesive film, and the backsheet are stacked and fed into a laminator for lamination. The laminator is a segmented laminator, meaning the stacked structure passes through each segment sequentially. Specifically, the first segment is 115℃~120℃ for 200s~300s; the second segment is 120℃~130℃ for 200s~300s; and the third segment is cooling for 150s~200s. After lamination, the top release layer is peeled off to obtain the anti-glare photovoltaic module. In other words, the anti-glare film attached to the cover glass of the photovoltaic module includes, along the incident light direction, a weather-resistant layer, a functional layer, and an adhesive layer.

[0073] It is understandable that the components of the adhesive layer will undergo a cross-linking reaction during the lamination process described above, thereby achieving a tight bond with the cover glass.

[0074] The following are examples of several anti-glare films, along with their performance analysis.

[0075] It should be noted that the refractive index of the three-layer anti-glare layer is mainly determined by the control of the resin matrix and nanoparticles in the composition forming the first, second, and third layers. Specifically, the content of the resin matrix is ​​increased, and the proportion of ordinary acrylic resin in the resin matrix is ​​increased to reduce the refractive index of the resin matrix. The proportion of added barium titanate nanoparticles is increased to further reduce the refractive index of the composition, thereby forming an anti-glare layer with a specific refractive index.

[0076] Example 1 In the three-layer anti-glare layer, the first layer has a refractive index of 1.48 and a thickness of 2μm; the second layer has a refractive index of 1.45 and a thickness of 2μm; and the third layer has a refractive index of 1.42 and a thickness of 2μm.

[0077] Example 2 In the three-layer anti-glare layer, the first layer has a refractive index of 1.47 and a thickness of 2μm; the second layer has a refractive index of 1.44 and a thickness of 2μm; and the third layer has a refractive index of 1.41 and a thickness of 2μm.

[0078] Example 3 In the three-layer anti-glare layer, the first layer has a refractive index of 1.49 and a thickness of 2μm; the second layer has a refractive index of 1.46 and a thickness of 2μm; and the third layer has a refractive index of 1.43 and a thickness of 2μm.

[0079] Comparative Example 1 In the three-layer anti-glare layer, the first layer has a refractive index of 1.48 and a thickness of 2μm; the second layer has a refractive index of 1.44 and a thickness of 2μm; and the third layer has a refractive index of 1.42 and a thickness of 2μm.

[0080] Example 4 The only difference between this embodiment and Embodiment 1 is that the thickness of the first layer is 2μm; the thickness of the second layer is 3μm; and the thickness of the third layer is 3μm.

[0081] Example 5 The only difference between this embodiment and Embodiment 1 is that the thickness of the first layer is 3 μm; the thickness of the second layer is 2 μm; and the thickness of the third layer is 3 μm.

[0082] Example 6 The only difference between this embodiment and Embodiment 1 is that the thickness of the first layer is 3 μm; the thickness of the second layer is 3 μm; and the thickness of the third layer is 2 μm.

[0083] Example 7 The only difference between this embodiment and Embodiment 1 is that the thickness of the first layer is 4 μm; the thickness of the second layer is 3 μm; and the thickness of the third layer is 3 μm.

[0084] Example 8 The only difference between this embodiment and Embodiment 1 is that the thickness of the first layer is 3 μm; the thickness of the second layer is 4 μm; and the thickness of the third layer is 3 μm.

[0085] Example 9 The only difference between this embodiment and Embodiment 1 is that the thickness of the first layer is 3 μm; the thickness of the second layer is 3 μm; and the thickness of the third layer is 4 μm.

[0086] Comparative Example 2 The only difference between this comparative example and Example 1 is that the thickness of the first layer is 1 μm; the thickness of the second layer is 1 μm; and the thickness of the third layer is 2 μm.

[0087] Comparative Example 3 The only difference between this comparative example and Example 1 is that the thickness of the first layer is 1 μm; the thickness of the second layer is 2 μm; and the thickness of the third layer is 2 μm.

[0088] Comparative Example 4 The only difference between this comparative example and Example 1 is that the thickness of the first layer is 4 μm; the thickness of the second layer is 4 μm; and the thickness of the third layer is 4 μm.

[0089] Comparative Example 5 The only difference between this comparative example and Example 1 is that the refractive index of the first layer is 1.42; the refractive index of the second layer is 1.45; and the refractive index of the third layer is 1.48.

[0090] Comparative Example 6 The only difference between this comparative example and Example 1 is that the first layer has a refractive index of 1.42 and a thickness of 3 μm; the second layer has a refractive index of 1.45 and a thickness of 3 μm; and the third layer has a refractive index of 1.48 and a thickness of 2 μm.

[0091] Test case The functional layers prepared in the above embodiments and comparative examples were bonded to the cover glass using an adhesive layer to form a sample. A weather-resistant layer was also provided on the side of the functional layer facing away from the adhesive layer. The adhesive layer was made of polyurethane-acrylate copolymer emulsion as the base material, with 1%–3% by mass of nano-montmorillonite added as a reinforcing phase, and had a thickness of 25 μm. The weather-resistant layer was made of polyester and had a thickness of 35 μm.

[0092] The visible light transmittance of the specimens was tested according to GB / T 2680-2021; the glare suppression rate of the specimens was tested according to ASTM E903-20.

[0093] Table 1 Test results for each embodiment and comparative example

[0094] Table 1 shows the test results of each embodiment and comparative example. Based on the data from Embodiments 1 to 3 and Comparative Example 1, when the difference in refractive index between layers is 0.03, the glare suppression rate reaches over 90%, and the visible light transmittance is high. In particular, when the refractive indices of the first to third layers are 1.48 / 1.45 / 1.42 (Example 1) and 1.47 / 1.44 / 1.41 (Example 2), the visible light transmittance reaches over 87%, while when the refractive index is 1.49 / 1.46 / 1.43 (Example 3), the visible light transmittance is only 79%. That is, although the glare suppression rate is high, the visible light transmittance is low. Furthermore, when the refractive index between layers does not decrease gradually, the glare suppression rate and visible light transmittance in Comparative Example 1 are both worse than in Example 1. Therefore, it can be seen that the refractive index of each anti-glare layer and the difference in refractive index between adjacent anti-glare layers affect the anti-glare performance and light transmittance of the anti-glare film.

[0095] Based on the data from Examples 1, 4-9, and Comparative Examples 2-4, it can be seen that when the total thickness of the functional layer is between 6 μm and 10 μm, both the glare suppression rate and visible light transmittance are excellent. However, when the total thickness of the functional layer is too thin (4 μm in Comparative Example 2 and 5 μm in Comparative Example 3), a sufficient refractive index gradient depth cannot be formed, resulting in poor anti-glare performance. When the total thickness of the functional layer is too thick (12 μm in Comparative Example 4), the reflectivity of the nanoparticles tends to saturate, and the anti-glare effect tends to stabilize, but the visible light transmittance decreases significantly. Therefore, the total thickness of the functional layer and the thickness of each anti-glare layer affect the anti-glare performance and light transmittance of the anti-glare film.

[0096] According to the data from Example 1 and Comparative Examples 5 to 6, as the refractive index increases from the first layer to the third layer, although the visible light transmittance is not significantly different from that of Example 1, the glare suppression rate is significantly reduced. Therefore, setting the refractive index of each anti-glare layer to decrease in a sequential gradient along the direction away from the incident light is more conducive to improving anti-glare performance.

[0097] Those skilled in the art should understand that the above embodiments are merely for illustrating the present invention and are not intended to limit the scope of the invention. Those skilled in the art can make other changes or modifications based on the above disclosure, and these changes or modifications still fall within the scope of the present invention.

Claims

1. An anti-glare film, characterized in that, It includes a functional layer comprising at least three anti-glare layers stacked together, wherein the refractive index of each anti-glare layer decreases sequentially along a direction away from the incident light.

2. The anti-glare film according to claim 1, characterized in that, The difference in refractive index between two adjacent anti-glare layers ranges from 0.02 to 0.

04.

3. The anti-glare film according to claim 1 or 2, characterized in that, The anti-glare layer has three layers, which are the first layer, the second layer, and the third layer along the direction away from the incident light; The refractive index of the first layer ranges from 1.47 to 1.49; the refractive index of the second layer ranges from 1.44 to 1.46; and the refractive index of the third layer ranges from 1.40 to 1.

43.

4. The anti-glare film according to claim 1, characterized in that, The total thickness of the functional layer ranges from 6 μm to 10 μm; and / or, The thickness of each anti-glare layer ranges from 2μm to 4μm.

5. The anti-glare film according to claim 3, characterized in that, The anti-glare layer is formed by curing the composition. By weight, the composition comprises: 49 to 66 parts of resin matrix, 9 to 24 parts of nanoparticles, 13 to 19 parts of diluent, 3 to 5 parts of photoinitiator, and 5 to 8 parts of solvent.

6. The anti-glare film according to claim 5, characterized in that, The resin matrix is ​​one or a combination of two of acrylic resin and silicone-modified acrylic resin in any proportion; and / or, The nanoparticles are barium titanate particles with a particle size of 50 nm to 100 nm; and / or, The diluent is one or a combination of two of trimethylolpropane triacrylate and ethoxylated trimethylolpropane triacrylate in any proportion; and / or, The photoinitiator is one or a combination of two of photoinitiator 1173 and photoinitiator 184 in any proportion; and / or, The solvent is a mixture of ethyl acetate and propylene glycol methyl ether acetate.

7. The anti-glare film according to claim 6, characterized in that, In the composition of the first layer, the resin matrix is ​​an organosilicon-modified acrylic resin, comprising 49 to 56 parts of the resin matrix, 19 to 24 parts of the nanoparticles, 13 to 19 parts of the diluent, 3 to 5 parts of the photoinitiator, and 5 to 8 parts of the solvent; and / or, In the composition of the second layer, the resin matrix is ​​a silicone-modified acrylic resin and an acrylic resin, the resin matrix is ​​56 to 61 parts, the nanoparticles are 13 to 18 parts, the diluent is 13 to 19 parts, the photoinitiator is 3 to 5 parts, and the solvent is 5 to 8 parts; and / or, In the composition of the third layer, the resin matrix is ​​silicone-modified acrylic resin and acrylic resin, the resin matrix is ​​58 to 66 parts, the nanoparticles are 9 to 15 parts, the diluent is 13 to 19 parts, the photoinitiator is 3 to 5 parts, and the solvent is 5 to 8 parts.

8. The anti-glare film according to claim 1, characterized in that, The anti-glare film also includes: A release layer, wherein the release layer is disposed on the incident light side of the functional layer; A weather-resistant layer is disposed between the release layer and the functional layer; An adhesive layer is disposed on the side of the functional layer opposite to the release layer; A protective layer is disposed on the side of the adhesive layer opposite to the functional layer.

9. The anti-glare film according to claim 8, characterized in that, The thickness of the release layer ranges from 26 μm to 78 μm; and / or, The thickness of the weather-resistant layer ranges from 25 μm to 45 μm; and / or, The thickness of the adhesive layer ranges from 18 μm to 28 μm; and / or, The thickness of the protective layer ranges from 25 μm to 75 μm; and / or, The release layer is composed of a PET film and a fluorinated release agent coating; and / or, The weather-resistant layer is made of polyester, acrylic, or epoxy-modified resin; and / or, The adhesive layer is prepared by adding nano-montmorillonite to a polyurethane-acrylate copolymer emulsion as the base material; and / or, The protective layer is made of polyethylene.

10. A photovoltaic module, characterized in that, It includes a cover glass and an anti-glare film disposed on the incident light side of the cover glass, wherein the anti-glare film is the anti-glare film according to any one of claims 1-7.